Exploring Commercial Development in Delhi's Mixed-Use Neighbourhoods: An Empirical Study - Uttam Kumar Roy; Puneet Mishra (Alanya Üniversitesi, 2024)
In rapidly urbanizing regions like Delhi, India, mixed-use developments have emerged as vital urban forms, driven by the organic conversion of residential spaces into commercial hubs. This study investigates the dynamics influencing commercial performance in both planned and unplanned mixed-use neighborhoods in North-West Delhi. Employing multiple linear regression analysis on data collected from 213 commercial establishments, the research identifies key factors such as commercial area characteristics, road accessibility, and the proximity of storeowners to their businesses as significant drivers of commercial growth. However, the study reveals that local customer bases are insufficient for sustaining high commercial performance, emphasizing the need for broader catchment areas. The findings contribute to urban planning discourse by providing empirical insights into the economic sustainability of self-organized mixed-use neighbourhoods. The study highlights the complex interplay between commercial development, spatial accessibility, and urban form, offering guidance for future urban planning strategies aimed at enhancing neighbourhood-level commercial performance. These results underline the importance of considering mixed-use dynamics in urban planning to support sustainable commercial growth and community vitality in rapidly evolving urban landscapes.